2020
DOI: 10.1186/s12866-020-02021-0
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota: effect of pubertal status

Abstract: Background The make-up of gut microbiota at different puberty stages has not been reported. This cross-sectional study analyzed the bio-diversity of gut microbiota at different puberty stages. Result The subjects (aged 5–15 years) were divided into non-pubertal (n = 42, male%: 66.7%) or pubertal groups (n = 47, male%:44.68); in both groups, Firmicutes, Bacteroidetes and Proteobacteria were the dominant phylum. There was no difference of alpha- and beta-diversity among disparate puberty stages. Non-pubertal s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 30 publications
1
26
1
1
Order By: Relevance
“…It is possible that obesity or, for example, a high-fat diet could alter microbiota progression during puberty. In contrast to our findings, a recent Chinese study showed a higher abundance of Clostridia in 5-year-olds compared with 15-year-olds 51 . In the 15-year-olds, several genera were found to be associated with the level of serum testosterone, but estradiol concentrations were not associated with microbiota composition 51 .…”
Section: Discussioncontrasting
confidence: 99%
“…It is possible that obesity or, for example, a high-fat diet could alter microbiota progression during puberty. In contrast to our findings, a recent Chinese study showed a higher abundance of Clostridia in 5-year-olds compared with 15-year-olds 51 . In the 15-year-olds, several genera were found to be associated with the level of serum testosterone, but estradiol concentrations were not associated with microbiota composition 51 .…”
Section: Discussioncontrasting
confidence: 99%
“…Eggerthellaceae , which has been linked to positive effects in lipid metabolism, was also inversely correlated with body weight gain in mice [ 60 ]. Although relatively little is known about the genera Adlercreutzia , it has been shown in pubertal human subjects to be positively associated with testosterone [ 61 ]. Adlercreutzia have also been shown to metabolize phytoestrogens [ 62 ] and it is therefore possible that this bacteria could be affected by sex hormones, although this warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It can be inferred that the abundance of Allobaculum is negatively correlated with intestinal permeability. All microorganisms of the genus Coprococcus can promote the production of short-chain fatty acids, which is good for the health of the host [ 48 ]. Kelly et al also found that a low abundance of Coprococcus can promote the development of IBD, which is also consistent with the results of this experiment [ 49 ].…”
Section: Discussionmentioning
confidence: 99%